In-situ measurements of energetic depth-limited wave loading. (August 2022) - Poncet, P.A.; Liquet, B.; Larroque, B.; D'Amico, D.; Sous, D.; Abadie, S.
Abstract: An extensive database of in situ measurements of wave impact pressure on the wall of a composite breakwater and associated explanatory variables (i.e., waves, wind, and water level) was collected in a particularly high-energy wave environment. Due to the bottom profile, which includes a wide mound of concrete blocks with a seaward edge that rises to the Lowest Astronomical Tide level over a large distance, most waves break before reaching the monitored barrier, making the data set representative of depth-limited wave loading. Maximum pressure is consistently found at the sensor position closest to the mean free surface, and statistically, a decrease of maximum pressure with the altitude is observed. Nevertheless, the database also shows a wide variety of vertical profiles of maximum pressure. A detailed analysis of the pressure signal shows that there are two impact classes associated with large pressure values. The first is mostly observed during stormy conditions with relatively slow pressure variations over time and a fairly uniform spatial distribution. The second class exhibits very limited pressure peaks in time and space and is most often observed during moderate sea states and high water levels. The pressure signals for each class agree well with the prediction of the PROVERB impact classification based on breakwater dimensions, water level, and wave parameters. Our dataset also shows the existence of impacts with simultaneous large pressure and rise time, which extends the range of the observed values of the pressure impulse already reported in-situ from 31000 Pa.s to 100000 Pa.s. For strong impacts that show regular upward propagation, the peak pressure propagation velocity was estimated and most values remain below 20 m/s. Finally, we performed a statistical analysis to relate the maximum pressure to a number of variables, including offshore wave parameters, water level, and wind parameters. The multiple linear regression model created confirms the dominant influence of wave height and the negligible influence of the wind on pressure maxima. The other wave parameters are still significant but of secondary importance. Finally, the upper bound of the 99% prediction interval predicts the maximum pressure given a set of wave and water level conditions with a good confidence level which is an encouraging result. Highlights: New extensive in-situ measurements of energetic depth-limited wave loading. New pressure impulse maximal values around 100000 Pa.s. Maximal impact pressure generated by storm waves or impulsive moderate wave impacts. Influence of wave height and wind on loading respectively, dominant and negligible. Statistical model predicts maximum pressure given wave and water level conditions.